A Large Cohort of Neurocysticercosis in Shandong Province, Eastern China, 1997–2015 - Huang, Xiaodan (Vector Borne Zoonotic Dis, 2019)
Neurocysticercosis (NCC) has a wide spectrum of neurologic and psychiatric manifestations, including epileptic seizures, high intracranial pressure, cognitive dysfunction, and meningoencephalitis. This study presents the clinical diagnosis of 2539 NCC patients in Shandong Province, Eastern China, from 1997 to 2015. The diagnosis was based primarily on clinical features, neuroimaging, immunology, and electroencephalogramy studies. In all age groups, seizures were found to be the most common manifestation, followed by headaches, memory loss, and limb numbness, and disability. After antiparasitic treatment, computed tomography and magnetic resonance imaging showed that most of the lesions had been completely absorbed in 2106 (82.95%) patients, most of the lesions had been absorbed and a small proportion was converted into calcifications in 433 (17.05%) cases. Indirect hemagglutination (IHA), enzyme-linked immunosorbent assay (ELISA), and circulating antigen (CAg) serum tests initially gave 76.45%, 86.37%, and 80.66% positive results, respectively. After antiparasitic therapy, the positive rates of the IHA, ELISA, and CAg tests were 74.77%, 84.70%, and 3.75%, respectively, showing no significant difference in antibody levels (p > 0.05), but a significant difference in CAg levels (p < 0.01). The clinical antiparasitic treatment of NCC with three to four courses of a combination of albendazole and praziquantel achieved satisfactory therapeutic efficacy.